Respuesta :
Answer:
x = 3 ± √5
Step-by-step explanation:
The expression (x - 3)² = 5 doesn't need completing the square to solve (this is the step after you finish completing the square):
Step 1: Square root both sides
x - 3 = ±√5
Step 2: Add 3 to both sides
x = 3 ± √5 = 0.76392, 5.23607
Step-by-step explanation:
There are two ways to solve this equation for x
Either you develop (x-3)^2 and then solve the quadratic equation
Or you can solve it this way :
(X-3)^2= 5
x-3 = + or - root square 5
So x = 3+ or - root square 5